3D direct writing egg white hydrogel promotes diabetic chronic wound healing via self-relied bioactive property. (March 2022) - Guo, Lingling; Niu, Xingtang; Chen, Xihang; Lu, Feng; Gao, Jianhua; Chang, Qiang
Abstract: Recent developments have evidenced the remarkable achievements of hydrogel combining drugs or growth factors delivery on diabetic chronic wound management. However, these techniques remain unsatisfactory and are impeded by high-cost, complex purification or fabrication, sophisticated drug loading, and lacking versatile therapeutic effects into one platform. Herein, a natural hydrogel is presented through feasible processing of fresh egg white, benefiting from the abundant protein contents and physical crosslinking, the gelation procedure of egg white from diverse species was demonstrated by the presented method, the egg white hydrogel can be kneaded to desired mechanical strength after infiltration of cation solution and directly wrote to well-defined architecture by the 3D printer. Meanwhile, the hydrogel possessed the inherent bioactive elements that stimulated the fibroblasts and adipose tissue-derived stem cells at the aspect of proliferation, migration, and functions without cytotoxicity which featured a similar cell-friendly substrate as Matrigel. Otherwise, the resulting 3D-printed hydrogels realized a proangiogenic effect and enhanced collagen deposition in vivo to promote the recovery of the normal and diabetic chronic wound in the absence of exogenous growth factors. Collectively, this hydrogel platform derived from abundant natural food provides an economical yet highly effective solution for chronic wound healing and may find more therapeutic roles in other biological utilizations and clinical practices. Graphical abstract: Image 1